If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 65 = 87 Reorder the terms: 65 + n = 87 Solving 65 + n = 87 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + n = 87 + -65 Combine like terms: 65 + -65 = 0 0 + n = 87 + -65 n = 87 + -65 Combine like terms: 87 + -65 = 22 n = 22 Simplifying n = 22
| 2(9/10f-1/3) | | x-y=120 | | 2(9/10x-1/2) | | 32xy=256 | | 5(2x-5)=7x+5-2 | | s-62=44 | | X^2=5m+6 | | (2x^2-5x-3)/(2x^2+11x+5) | | 290/4 | | 8n+1=24 | | A=r/2h | | 2w+80+9w=-9+3w-7 | | f(-3)=4*-3-3 | | 4(4+18)/(10-9) | | (2x^6)/(3y^4) | | x^2+x=19 | | x^2+x=19 | | 5/6/4 | | n-12=36 | | (9x^2-3x+11)/(x-6) | | x2-8x+16/2x-8 | | 2(8+w)=22 | | 49=4y+13 | | 5x^2-28x-12= | | 4n-8/-2=12 | | 2+6/s=5 | | 7x-21=1 | | 7.6x+8.37=-56.99 | | x-7=6.16 | | 7+n-6=1 | | 3(2x-2.3)=2x-6.9 | | 3y-8=-5 |